Edukasi Slow Deep Breathing pada Penderita Hipertensi di Kelurahan Kasang Kumpeh - Faridah Faridah; Wanti Hasmar; Iin Indrawati (Jurnal Abdimas Kesehatan (JAK), 2022)
Many Indonesians suffer from hypertension, and the number of instances continues to rise as people get older. Patients with hypertension, if not treated for a long time, can develop a variety of consequences that might lead to death; consequently, careful management is required to ensure that patients do not develop complications that aggravate their hypertension. Deep breathing exercise, specifically deep and slow breathing exercises, is one of the physiotherapy techniques that can be used to treat hypertension. The goal of this community service project is to deliver health education to recitation mothers in Kasang Kumpeh Jambi Village about how to self-manage hypertension at home by doing calm deep breathing. The implementation of this community service will take place in October 2021.Counseling about hypertension, the hazards of hypertension, and offering information on how to practise calm deep breathing were all part of this community service programme. In addition, as a form of community service, a demonstration of blood pressure checks was held. The community's rising independence on the importance of managing blood pressure and preventing the hazards of hypertension can be recognised as a result of this action.